In vitro effects of rabeprazole on human pylorus tone - Yaşar, Necdet Fatih; Polat, Erdal; Duman, Mustafa; Dağdelen, Meltem; Günal, Mehmet Yalçın; Uzun, Orhan; Akyüz, Cebrail; Peker, Kıvanç Derya; Yol, Sinan (The Korean Society of Neurogastroenterlogy and Motility, 2015)
Background/Aims It has been reported that proton pump inhibitors induce relaxation in different types of smooth muscles. The aim of this study is to investigate in vitro effects of proton pump inhibitors on human pylorus muscle. Methods Pyloric sphincters were studied in 10 patients who were operated for stomach cancer. In isolated organ bath, control and response to rabeprazole were recorded following contraction with carbachol. During the treatment experiment, while distilled water was applied during the control experiment in every 5 minutes, rabeprazole was administered in every 5 minutes at doses of 10(-6), 10(-6), 10(-4), and 10(-3) M respectively. Contraction frequencies, maximum contraction values and muscle tones were measured. Results The contraction frequencies in the control group were greater than the rabeprazole group in the second, third and fourth intervals while the maximum contraction values in the rabeprazole group were lower in the fourth interval. Even though muscles tones were not different in both groups during all intervals, it was remarkable that the muscle tone was significantly decreased in the rabeprazole group during the fourth interval compared to the first and second intervals. Conclusions In the present study, high doses of rabeprazole reduced contraction frequencies, maximum contraction values, and muscle tone of human pylorus.
WOS: 000352750400009
PubMed ID: 25843074
Keywords: Muscle Tonus; Proton Pump Inhibitors; Pylorus; Rabeprazole